Pengaruh Pengalaman Masa Nifas Terhadap Budaya Dalam Perawatan Masa Nifas Di PMB Valen Aprilia R - Farlikhatun , Lili; Aprilia Romadiana , Valen (Jurnal Keperawatan Muhammadiyah, 2024)
Background: In terms of maternal care during pregnancy, childbirth and postpartum, Indonesian people cannot be separated from behavior and habits based on customs or culture which are believed to provide benefits and positive impacts. Community beliefs, traditions and culture in the care of postpartum mothers are still widely found in the community. The community believes that the culture of caring for postpartum mothers has many positive and beneficial impacts on them.Research Objective: To determine the influence of postpartum experience on culture in postpartum care at PMB Valen Aprilia R.Research Method: Cross Sectional with the population in this study being postpartum mothers in the PMB Valen Aprilia R work area in November 2023 as many as 34 people. The sample was determined using purposive sampling of 30 people.Research Results: The correlation value obtained a result of 0.531, which means that the influence of postpartum experience on culture in postpartum care is very strong, which means mothers who have good knowledge of postpartum experience tend to have a positive attitude towards culture in postpartum care. The results showed that the significance level was 0.003, which was lower than 0.05. The results of this research show thatConclusions and Suggestions: There is an influence of postpartum experience on culture in postpartum care at PMB Valen Aprilia R in 2023. In order to improve the quality of services, provide guidance to the community such as PKK mothers, posyandu cadres and also the surrounding community, especially providing health education for postpartum mothers in choosing or carrying out cultural practices. To reduce the risk of health problems in postpartum mothers and their babies.